Desacralization of Islamic Values in 'Bismillah Cinta': Semiotics Analysis in the Character of Ustadz Rehan - Wahyudin, Aep; Supratman, Lucy Pujasari (Proceedings of International Conference on Da'wa and Communication, 2021)
This study aims to analyze the construction of an ustadz (Moslem teacher) in the religious drama series (sinetron) 'Bismillah Cinta'. The research is focussed on exploring the desacralization aspect related to the commodification of the ustadz character shown in 'Bismillah Cinta' drama series. The researchers used qualitative research method with the semiotic approach of Charles Sanders Pierce. There are 5 scenes that have been selected based on the criteria of the desacralization in the ustadz character. Data collection techniques were carried out through observation and documentation. The results showed that the commodification of the ustadz character in the drama series of 'Bismillah Cinta' did not reflect an ustadz who hold the role in keeping peaceful and harmony with the religious messages.